Progress in Flight Physics – Volume 7 2015
DOI: 10.1051/eucass/201507329
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the turbulent wake flow of a generic space launcher configuration

Abstract: The turbulent wake of a generic space launcher at cold hypersonic freestream conditions is investigated experimentally and numerically to gain detailed insight into the intricate base §ow phenomena of space vehicles at upper stages of the §ight trajectory. The experiments are done at Ma ∞ = 6 and Re D = 1.7 · 10 6 m −1 by the German Aerospace Center (DLR) and the corresponding computations are performed by the Institute of Aerodynamics Aachen using a zonal Reynolds-averaged Navier Stokes / Large-Eddy Simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This peak is found by several authors [6,10,15,19]. For hypersonic base flows Statnikov et al [25] and Saile et al [28] found similar peaks. With jet flow we obtained an additional peak at higher Strouhal numbers.…”
Section: Signal Qualitysupporting
confidence: 78%
See 1 more Smart Citation
“…This peak is found by several authors [6,10,15,19]. For hypersonic base flows Statnikov et al [25] and Saile et al [28] found similar peaks. With jet flow we obtained an additional peak at higher Strouhal numbers.…”
Section: Signal Qualitysupporting
confidence: 78%
“…The results with jet shows additional high frequencies information. Statnikov et al [25,26] performed numerical flow analysis of the wake of a generic launcher model at M = 6 including dynamic mode decomposition analysis. Using this analysis they associated dominating frequencies to wake flow phenomena, i.e., longitudinal pumping of the cavity, a swinging mode of the shear layer and a radial flapping motion of the shear layer.…”
mentioning
confidence: 99%
“…Pain et al [13] noticed that its influence is felt in the regions close to the separation and mean reattachment points, whereas Kiya and Sasaki [42] observed it close to the separation point and relate the vertical motion of the shear layer to the streamwise oscillations of the instantaneous reattachment point. However, Saile et al [20] and Statnikov et al [21][22][23] relate the low frequency to the motion of the large vortices within the recirculation bubble. In the current study, the low-frequency broadband peak attains its maximum amplitude at x/H=3.38, which is neither close to the separation nor the reattachment points.…”
Section: Fig 8 Spectra On Rearbody At Different Downstream Locations ...mentioning
confidence: 99%
“…2). Statnikov et al [22][23] associated these frequencies with the vortex motions within the recirculation bubble. Cherry et al [45] stated that the low frequencies scale well with the length of the recirculation bubble, or the mean reattachment length.…”
Section: Spectra Of M∞=12mentioning
confidence: 99%
See 1 more Smart Citation